The Carnival as an Instrument to Exorcize the Industrial Past. The Experience of Ottana (Italy) - Andrea Francesco Zedda (Cuadernos de Arte de la Universidad de Granada, 2017)
In this article, based on a field study carried out in Ottana, a town in the center of Sardinia (Italy), I propose to reflect on the peculiar process of “patrimonialization” that has interested the Ottana community after the industrialization, led by the State, in the seventies. Taking as an object of study the artistic productions linked to the local Carnival of “boes e merdules”, I analyze the function of the art in the process of exorcization of the industrial past, already failed one decade ago. What emerges is a unique identity configuration of the heritage, strictly linked to the industrial event, which will allow us to observe the relationship of the community with the otherness of the State.